2015
DOI: 10.1080/15384101.2015.1056948
|View full text |Cite
|
Sign up to set email alerts
|

Role of stress-activated OCT4A in the cell fate decisions of embryonal carcinoma cells treated with etoposide

Abstract: Tumor cellular senescence induced by genotoxic treatments has recently been found to be paradoxically linked to the induction of “stemness.” This observation is critical as it directly impinges upon the response of tumors to current chemo-radio-therapy treatment regimens. Previously, we showed that following etoposide (ETO) treatment embryonal carcinoma PA-1 cells undergo a p53-dependent upregulation of OCT4A and p21Cip1 (governing self-renewal and regulating cell cycle inhibition and senescence, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 64 publications
(55 reference statements)
4
49
0
Order By: Relevance
“…This was downstream of activated TP53, as both p21 and partly OCT4A became downregulated after TP53 RNAi silencing ( Figure 2C) [45]. Further study [46] revealed that p53-activated OCT4A down-regulated p21CIP1, moderating its expression and preventing cells from precipitating terminal senescence or apoptosis (Figure 2D), thus providing the opportunity for repair. Downregulation of p21 via OCT4 was previously shown in ESC [47].…”
Section: Ovarian Germline Cells Challenged By Genotoxic Stress Displamentioning
confidence: 90%
See 4 more Smart Citations
“…This was downstream of activated TP53, as both p21 and partly OCT4A became downregulated after TP53 RNAi silencing ( Figure 2C) [45]. Further study [46] revealed that p53-activated OCT4A down-regulated p21CIP1, moderating its expression and preventing cells from precipitating terminal senescence or apoptosis (Figure 2D), thus providing the opportunity for repair. Downregulation of p21 via OCT4 was previously shown in ESC [47].…”
Section: Ovarian Germline Cells Challenged By Genotoxic Stress Displamentioning
confidence: 90%
“…The bizarre duality of OCT4A with p21CIP1 was subdued and cell cycle in the PA1 clones returned to normal, on days 7-14 (Figure 2A), while silencing of stress-activated OCT4A prevented recovery [46]. This transient undecided state in G2 arrest, between true senescence and true self-renewal, was thus lasting as long as wtTP53 was activated by the DNA DSB.…”
Section: Ovarian Germline Cells Challenged By Genotoxic Stress Displamentioning
confidence: 96%
See 3 more Smart Citations